Reliability of human estimates of the presence of pups and the number of wolves vocalizing in chorus howls: implications for decision-making processes - Palacios, Vicente; Font, Enrique; García, Emilio José; Svensson, Linn; Llaneza, Luis; Frank, Jens; López-Bao, José Vicente (European journal of wildlife research, 2017)
Management decision-making processes require reliable tools providing information on the distribution, abundance, and trend of populations. Wolves vocalize in response to human imitations of howls. Traditionally, this phenomenon has been the basis of a widespread monitoring tool to assess the reproductive status in a wolf pack, as well as to estimate the minimum number of individuals in the pack: the elicited-vocalization technique. However, despite its broad use, only a few attempts to quantify its accuracy have been made so far. Here, we carried out a test to evaluate the accuracy of estimates obtained from the elicited-vocalization technique. We administered “chorus tests” to 205 human subjects, 182 rangers—with different level of experience with wolves—and 23 subjects with no previous experience with the species. We found that the estimates of the number of wolves participating in a chorus were not accurate, regardless of the experience of the listener (the correct number of wolves was only determined in 32% of tests). Listeners, however, identified pups vocalizing 98% of the times when there were pups in the chorus. They also reported the presence of pups when they were not present with a high frequency (71%). Estimating the number of individuals by the unaided human ear is flawed because of the bias inherent in the elicited-vocalization technique. Howling surveys have a low degree of selectivity to confirm the presence of pups. Thus, we make recommendations to improve the elicited-vocalization technique as a tool to monitor the presence of pups.